Anticholesterolemic Activity of Three Vegetal Extracts (Artichoke, Caigua, and Fenugreek) and Their Unique Blend - Frigerio, Jessica; Tedesco, Erik; Benetti, Federico; Insolia, Violetta; Nicotra, Giovanna; Mezzasalma, Valerio; Pagliari, Stefania; Labra, Massimo; Campone, Luca (Frontiers in Pharmacology, 2021)
Hepatic-related diseases are a thorn on the side of national health institute around the globe. Indeed, the liver is responsible for many critical metabolic pathways and, among them, lipid homeostasis regulation is one of the most important. Its dysregulation could lead to a generalized increase in blood cholesterol and lipid levels (hyperlipidemia), which could lead to atherosclerotic plaque formation. As such, hypercholesterolemia tightly links liver dysfunction to cardiovascular diseases (CVD), and in particular to coronary artery diseases (CAD). Currently, statins administration and monacolin K consumption are the main therapy proposed to counter this alarming connection, but relevant side-effects are known. To overcome this issue, safe nutraceutical formulations and/or the vegetal extracts, endowed with anticholesterolemic activity, could be instrumental in hypercholesterolemia prevention and treatment. In the present work, the anticholesterolemic efficacy of artichoke, caigua and fenugreek extracts and their unique blend, ACFB, was assessed by an in vitro approach. Vegetal extracts and ACFB are safe and have anticholesterolemic activity. Consequently, they represent a valid phytotherapy for hypercholesterolemia and related conditions.